OPTIMALISASI CUSTOMER RELATIONSHIP MANAGEMENT (CRM) DALAM MENINGKATKAN LOYALITAS SANTRI DAN WALI SANTRI DI PONDOK PESANTREN - Putri, Tasya Nabila (STKIP Pesisir Selatan, 2025)
Optimizing CRM in Islamic boarding schools is not only about implementing new technology, but also about how the boarding school can build and maintain good relationships with all stakeholders, so that it can provide satisfaction and increase loyalty. This study aims to analyze (1) Optimizing HR performance in increasing loyalty in Diniyyah Putri Islamic boarding schools and Al Hikmah Islamic boarding schools (2) Optimizing CRM processes in increasing loyalty in Diniyyah Puyri Islamic boarding schools and Al Hikmah Islamic boarding schools (3) Optimizing CRM technology in increasing loyalty in Diniyyah Puyri Islamic boarding schools and Al Hikmah Islamic boarding schools. This study uses a qualitative descriptive research type. Data sources from primary and secondary data. Based on the results of the study, it shows that (1) Optimizing HR performance is carried out by providing socialization of the system that will be used and training for each field. (2) The CRM process provides convenience for both stakeholders of the boarding school to provide more effective and efficient services and guardians of students in receiving more transparent information both before (3) The technology applied in CRM through a website and application software-based system.